1994
DOI: 10.1017/s0022112094003083
|View full text |Cite
|
Sign up to set email alerts
|

Experiments in a boundary layer subjected to free stream turbulence. Part 1. Boundary layer structure and receptivity

Abstract: The modification of the mean and fluctuating characteristics of a flat-plate boundary layer subjected to nearly isotropic free stream turbulence (FST) is studied experimentally using hot-wire anemometry. The study is focussed on the region upstream of the transition onset, where the fluctuations inside the boundary layer are dominated by elongated flow structures which grow downstream both in amplitude and length. Their downstream development and scaling are investigated and the results are compared with those… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

63
235
3

Year Published

2000
2000
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 317 publications
(301 citation statements)
references
References 11 publications
63
235
3
Order By: Relevance
“…Matsubara & Alfredsson's data demonstrated that the spanwise scale of the disturbances approaches the boundary layer thickness downstream after an initial adjustment, and that the energy of the streamwise velocity fluctuation grows linearly with downstream distance, which is consistent with observations in previous studies, e.g. Westin et al (1994). The proportionality constants, however, vary from one experiment to another.…”
Section: Bypass Transitionsupporting
confidence: 87%
“…Matsubara & Alfredsson's data demonstrated that the spanwise scale of the disturbances approaches the boundary layer thickness downstream after an initial adjustment, and that the energy of the streamwise velocity fluctuation grows linearly with downstream distance, which is consistent with observations in previous studies, e.g. Westin et al (1994). The proportionality constants, however, vary from one experiment to another.…”
Section: Bypass Transitionsupporting
confidence: 87%
“…Ricco [42] (hereafter referred to as R9), by adopting LWG99's asymptotic approach, showed that a balance between the free-stream pressure fluctuations and the streamwise velocity fluctuations is relevant for the formation of the streak fluctuations in the outer part of the boundary layer. A realistic streak profile along the whole wall-normal extent of the boundary layer was obtained by R9 and good agreement with the experimental data by Westin et al [56] was shown. Ricco & Dilib [43] employed R9's approach to show that the peak of the streak amplitude in the boundary-layer core may be completely suppressed if intense wall transpiration is applied and Ricco and co-authors [47,46,45] have studied the Klebanoff modes in compressible boundary layers.…”
Section: Theoretical Framework For the Laminar Streakssupporting
confidence: 81%
“…The objective of the analysis is to find the initial velocity profile near the leading edge that maximizes a specified cost function, which may represent the energy of the perturbation within the entire viscous layer or at a specified downstream distance. When the peak disturbance is normalized, the wallnormal profile agrees well with the Taylor-Stewartson mode and with the experimental rms profiles of the streamwise velocity in the boundary-layer core [56,33], although no comparison on the downstream evolution has been carried out.…”
Section: − the Taylor-stewartson Theorysupporting
confidence: 58%
See 1 more Smart Citation
“…Hultgren & Gustavsson 1981;Westin et al 1994;Jacobs & Durbin 2001). Their elongated appearance is explained by the rapid distortion theory (Phillips 1969), and their spanwise scale can be predicted using transient growth analysis (Butler & Farrell 1992).…”
Section: Introductionmentioning
confidence: 99%